INFLUENCE OF INFLAMMATORY PERIODONTAL DISEASES ON THE PROTEOMIC ANALYSIS - I. V. Reshetov; E. V. Kochurova; V. N. Nikolenko; A. A. Mukhanov (Сеченовский вестник, 2017)
In this work, we study the local immunity of the mucous membrane of the oral cavity in patients with compromised dental status in squamous cell carcinoma by examining the expression of matrixins and tumor markers.In the role of the constituent characteristics of dental status were examined: the use of removable and ﬁxed dentures, dental caries, hard and soft dental plaque, sharp edges of ﬁllings, chipped and cracked teeth and broken dentures. Obtained results were compared with those in patients with sanitized oral cavity, as with squamous cell carcinoma of the mucosa of the oral cavity and of the control group.Noninvasive testing has become increasingly popular and it is relevant to study local immunity through the use of free (unstimulated) saliva and identify biomarkers of type metalloproteinases and tumor markers.